Generative AI in higher education: Perspectives of students, educators and administrators (Journal of Applied Learning and Teaching, 2024)
With Generative AI’s (GenAI) rapid development and the ability to generate sophisticated human-like text, it has evolved as a powerful technology in various domains. However, its application in the education domain was initially met with resistance due to concerns about disrupting traditional learning and assessment methods, raising questions about academic integrity, and provoking ethical dilemmas related to data privacy and bias. Many schools, higher educational institutions, and governments initially chose to ban the use of GenAI tools due to the disruptions they caused to learning and teaching practices, only to rescind their bans later. This study conducts a literature review to investigate GenAI tools from the perspectives of key stakeholders in the educational domain—students, educators, and administrators—highlighting their benefits while identifying challenges and limitations. The review found several benefits of using GenAI, such as personalised learning, immediate support, language support, and reduced administrative workload. This paper also provides usage guidelines for stakeholders and outlines future research areas to support GenAI adoption in higher education. Our findings indicate that most studies involving students had a positive view of using GenAI. There is a noticeable gap in research focusing on administrators, highlighting the need for further investigation.